1997
DOI: 10.1002/(sici)1098-2396(199712)27:4<267::aid-syn1>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Target-dependent synaptogenesis: Inductive effect of pituitary melanotrophs on their central innervation

Abstract: The glandular activity of the vertebrate pituitary intermediate lobe (IL) is regulated by direct cellular innervation, in contrast with the purely humoral regulation of adjacent pituitary anterior lobe (AL). Thus in the rat IL, melanotrophs receive a dopaminergic and GABAergic innervation from the basal hypothalamus, which tonically inhibit their glandular activity. We studied this model of neuron-target interactions in cocultures in defined medium of fetal hypothalamic neurons with neonate pituitary glandular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Although POMC is also expressed in situ by a subpopulation of neurons in the arcuate nucleus (Mansour et al, 1988), in our cultures of hypothalamic neurons alone, neither MSH immunoreactivity nor secretion of the peptide in the culture medium was detectable. In co-cultures with nb NIL cells, the level of secreted αMSH (about 1 nM/day and well, René et al, 1997) is only attributable to melanotrophs, since neurons are not immunoreactive for αMSH. It is now well established that POMC-derived peptides can exert neurotrophic effects on several areas of the central nervous system (for reviews see Strand et al, 1993;Darlington et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although POMC is also expressed in situ by a subpopulation of neurons in the arcuate nucleus (Mansour et al, 1988), in our cultures of hypothalamic neurons alone, neither MSH immunoreactivity nor secretion of the peptide in the culture medium was detectable. In co-cultures with nb NIL cells, the level of secreted αMSH (about 1 nM/day and well, René et al, 1997) is only attributable to melanotrophs, since neurons are not immunoreactive for αMSH. It is now well established that POMC-derived peptides can exert neurotrophic effects on several areas of the central nervous system (for reviews see Strand et al, 1993;Darlington et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In our conditions, the DA neurons contacting the melanotrophs are also immunoreactive for GAD, as those innervating the IL in situ . Moreover, in co‐cultures of foetal hypothalamic neurons with nb IL cells, we have recently reported the establishment of target‐dependent and, to some extent, neuron‐selective synapses (Egles et al 1997) between GABAergic/DA neurons and melanotrophs, and demonstrated their functionality (Poisbeau et al 1996). These observations clearly suggest neurotrophic effects of the target (melanotrophs) on their afferent neurons which may most probably correspond to the population of dopaminergic/GABAergic neurons originating from the A14 hypothalamic nucleus, which innervate the melanotrophs in situ .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations